Pembuatan Bahan Ajar Digital Akuntansi Dasar Untuk Sekolah Menengah Kejuruan Swasta Patria Dharma Selat Panjang - Widijaya Widijaya; Wiwy Riana (ConCEPt - Conference on Community Engagement Project, 2021)
The implementation of the activity of making digital teaching materials has the aim of being able to help the community, especially schools, to get alternative sources of digital learning that can be used especially during this pandemic. Patria Dharma Vocational Private High School is the object of this digital teaching material creation activity. This activity uses several data collection techniques in the form of observation, interviews, and documentation. The process of designing this digital material, it goes through many processes consisting of meetings with the school to discuss the subjects that need assistance, the process of finding material that is under the curriculum and competencies that must be achieved, consultation with the teacher on the material being sought has met the standards of the school, a compilation of PPT using Microsoft PowerPoint 2019 tools, making learning videos in the form of animated videos using Animaker tools and finally the output produced is sent to the supervisor for evaluation. The resulting output has a very big impact that can be felt by the school, such as teachers who teach Basic Accounting subjects that feel helped because with this digital teaching material it can make students get the opportunity to learn independently, students enjoy the process more learning and become more focused because of the teaching materials made in the form of interesting, animated videos. Suggestions are given for the making of digital teaching materials in the future that can be made in various language versions, such as in English, and case studies should be carried out to deepen the information needed to create better teaching materials in the future.